Independent Ireland in comparative perspective - Kevin H. O'Rourke (University College Dublin, UCD School of Economics, 2016)
This paper surveys independent Ireland's economic policies and performance. It has three main messages. First, the economic history of post-independence Ireland was not particularly unusual. Very often, things that were happening in Ireland were happening elsewhere as well. Second, for a long time we were hampered by an excessive dependence on a poorly performing UK economy. And third, EC membership in 1973, and the Single Market programme of the late 1980s and early 1990s, were absolutely crucial for us. Irish independence and EU membership have complemented each other, rather than being in conflict: each was required to give full effect to the other. Irish independence would not have worked as well for us as it did without the EU; and the EU would not have worked as well for us as it did without political independence.
Keywords: 330